Identification of the molecular partners that regulate MEIS1A function - Ravishankar Chandrasekaran (2014)
Meis1 encodes a homeodomain-containing transcription factor which performs a vital role during embryonic development as well as in adult physiological processes, particularly hematopoiesis. It is an oncogene in many kinds of leukemia, most notably acute myeloid leukemia (AML) and mixed lineage leukemia (MLL) as well as solid tumors like neuroblastoma. In addition, Meis1 has been implicated in genetic disorders like restless leg syndrome. MEIS1 functions upstream of many target genes to regulate their expression. HOX and PBX proteins are the most important and well-studied interaction partners of MEIS1. Recently, however, MEIS1 has been shown to interact with CRTC transcription factors and function in a PKA-dependent signaling pathway. Considering the significance and the diversity of the processes regulated by MEIS1, we hypothesized that it could interact with a large repertoire of proteins in order to carry out its functions. Hence my work involved the purification and identification of novel interaction partners of MEIS1A, the widely expressed isoform of MEIS1. To accomplish this goal, I used a recently described technique for the purification of interaction partners. It involved the in vivo biotinylation of MEIS1A followed by a single-step purification of the MEIS1A-interacting proteins using streptavidin-affinity purification. Using mass spectrometry, I identified approximately 40 different proteins that specifically co-purified with MEIS1A. Through co-immunoprecipitation assays, I validated the interaction of MEIS1A with some of these proteins including NONO, NOP56, NOP58, CBX3 and MLL1. I was also able to show that the interaction with NONO, NOP56 and NOP58 is conserved among other MEIS1-related proteins like PKNOX1 and PKNOX2. NONO is of interest because of its reported interaction with CRTC1. I was able to show that NONO does not mediate the interaction between CRTC1 and MEIS1A. In addition, NONO does not contribute to the transactivation potential of MEIS1A under our experimental conditions. The physiological relevance of the MEIS1A-NONO interaction is therefore yet to be understood. The MEIS1A-MLL1 interaction that I identified was very interesting because both proteins play physiologically important roles during hematopoiesis and leukemia and function in a common pathway. We were able to show that MLL1 and MEIS1 interact endogenously in RS4;11 cells. The MEIS1A interaction is retained by MLL-AF4 which is a leukemogenic fusion protein of MLL1. I was also able to map the interaction of MLL1 to the C-terminal region of MEIS1A. Together, my data provide insight into the interactome and mechanisms of MEIS1A function, and open multiple avenues for further investigation.